Formulation, process development and evaluation of artemether and lumefantrine soft gelatin capsule - A Patel; A Lodha; J Chaudhuri; P Jadia; T Joshi; J Dalal (Wolters Kluwer Medknow Publications, 2012)
Artemether and Lumefantrine capsules are indicated for the treatment of P. falciparum malaria cases resistant to both chloroquine and sulphadoxine, pyrimethamine combination. Both artemether and lumefantrine act as blood schizontocides. Artemether is a sesquiterpene lactone derived from artemisinin. Artemisinin is a compound derived from the sweet wormwood plant and has been used for centuries in traditional Chinese medicine to treat fever. Lumefantrine is a synthetic aryl-amino alcohol antimalarial (quinine, mefloquine and halofantrine are members of the same group). Artemether is absorbed fairly rapidly with peak plasma concentrations reached about 2 hours after dosing. Absorption of lumefantrine, a highly lipophilic compound, starts after a lag period of up to 2 hours, with peak plasma concentration about 6-8 hours after dosing. In order to overcome this problem, we have observed that when the drug is given in the soft gelatin dosage form, the bioavailability of the drug is increased. Thus, increasing the absorption of the drug and peak plasma concentration is reached earlier then the conventional dosage form.